Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing - Lee, Roger (Studies in Computational Intelligence,, 2019)
This edited book presents the scientific outcomes of the 19th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD 2018), which was held in Busan, Korea on June 27-29, 2018. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. The book includes research findings on all aspects (theory, applications and tools) of computer and information science and discusses the practical challenges encountered along the way and the solutions adopted to respond to them. The book includes 13 of the conference's most promising papers.